ESL, EFL, EIL Revisited: Investigation, Evaluation and Justification of a Shift in the Current ELT Models in Iran - Talebinezhad, Mohammad Reza; Aliakbari, Mohammad (Linguistik Online, 2002)
English language teaching in Iran has usually been considered an EFL model. This position, though common and widespread, seems to need revision in several grounds. Through comparing EFL, ESL and EIL (English as an international language) models based on Smiths (1978) comparative study, the present article reveals that the ELT in Iran no longer follows EFL model. The comparative evaluation makes it clear that in terms of most categories ELT in Iran shows the characteristics of EIL. Therefore, through characterizing it as a developmental process along a continuum towards EIL, the present study argues for instances of paradigm shift and thus claims that the ELT context in Iran is ripe for revision.